ENSURING SUSTAINABLE DEVELOPMENT OF TRANSNATIONAL CORPORATIONS - Імнадзе, Іраклій Н. (Journal of Strategic Economic Research, 2023)
The presented paper examines the main features of the development of transnational corporations, their characteristic features of activity on the global world stage, and defines the main trends in the direction of the development of transnational corporations. The purpose of the presented work is to determine the main areas of activity of transnational corporations in terms of ensuring sustainable development. The main methods of research are analysis and synthesis for determining the main features of the development of transnational corporations, methods of deduction and induction for researching the activities of transnational corporations on the world global market, and a graphic method for visual display of research. The sustainable development of transnational corporations is an important task to ensure their successful functioning in the long term. The peculiarity of sustainable development is that corporations ensure their growth and prosperity, taking into account the impact of their actions on the social, economic and environmental environment. Transnational corporations must ensure efficient use of resources, optimization of production processes and stimulate innovative development. This helps ensure the stability of the company in the market and maintain a competitive advantage. Transnational corporations must take into account the social aspects of their activities, in particular, the creation of quality jobs, ensuring fair wages, respecting the rights of workers, and developing a responsible business culture. Transnational corporations should take care of the environmental consequences of their activities and work to reduce the negative impact on the environment. The use of green technologies, the implementation of energy-efficient projects and the reduction of emissions of harmful substances can help preserve natural resources and reduce the impact on climate change. The sustainability of the development of a transnational corporation depends on cooperation with all interested parties, such as public organizations, government institutions, local communities and other business partners. Interaction with these parties allows you to ensure harmony between the interests of different groups and maintain a positive perception of the corporation’s activities. In general, the sustainable development of transnational corporations requires an integrated approach and attention to economic, social and environmental aspects of activity. Only by ensuring a balance between corporate profitability and a responsible attitude to society and nature can transnational corporations ensure sustainable success and prosperity in the long term.